2014
DOI: 10.1111/ecc.12261
|View full text |Cite
|
Sign up to set email alerts
|

The effect of docetaxel on developing oedema in patients with breast cancer: a systematic review

Abstract: Docetaxel is extensively used in chemotherapy for the treatment of breast cancer. Little attention has been given to oedema as a possible side effect of docetaxel-containing therapies. Until now, no review was conducted to evaluate docetaxel-containing therapies versus docetaxel-free therapies on the magnitude of the risk of developing oedema. In this systematic review, we investigated the risk of developing oedema in patients being treated for breast cancer with or without docetaxel. In this systematic litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In most situations, several mechanisms may occur and contribute synergistically to oedema genesis. In addition to aggressive fluid resuscitation and preparation T A B L E 1 Causes of peripheral edema 10,12 Mechanism Cause Force involved Increased capillary permeability (as these drugs are responsible for capillary leak syndrome) Taxanes: 38,39 docetaxel, paclitaxel -increased capillary permeability 38,39 -lymphedema 40,41 through antilymphangiogenic effects of VEGFR-3/VEGFC pathway inhibition 40 -heart failure 4 Protein kinase inhibitors ALK: 42…”
Section: Drug-induced Peripheral Oedemamentioning
confidence: 99%
“…In most situations, several mechanisms may occur and contribute synergistically to oedema genesis. In addition to aggressive fluid resuscitation and preparation T A B L E 1 Causes of peripheral edema 10,12 Mechanism Cause Force involved Increased capillary permeability (as these drugs are responsible for capillary leak syndrome) Taxanes: 38,39 docetaxel, paclitaxel -increased capillary permeability 38,39 -lymphedema 40,41 through antilymphangiogenic effects of VEGFR-3/VEGFC pathway inhibition 40 -heart failure 4 Protein kinase inhibitors ALK: 42…”
Section: Drug-induced Peripheral Oedemamentioning
confidence: 99%
“…In addition to surgery, chemotherapeutic drugs, such as oxaliplatin, 5-fluorouracil, and irinotecan, are frequently used in first-line treatment of CRC 4. However, systemic administration of chemotherapeutic drugs generally leads to dose-limiting toxicity in non-target tissues and organs 5, 6, while treatment by the most preferable and acceptable route of oral delivery more often results in unsatisfactory bioavailability and serious side effects, such as mucositis, edema, and diarrhea 7-9.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to their study, the prevalence of lymphedema at the endpoint in our study is higher. This could be the effect of the adjuvant treatment with TAC as suggested in a recent study indicating docetaxel as important risk factor for onset of lymphedema, with a chance of developing lymphedema being 4.8 times higher when compared to other treatment regimens [ 10 ] and reported in earlier studies as well [ 7 9 , 11 14 ]. Compared to our study, earlier studies on TAC as a risk factor for lymphedema reported a higher prevalence of lymphedema over two or more years after treatment with TAC with 33.5% [ 12 ], 42.2% [ 14 ], and 32% after treatment, declining to 23% at 6 months [ 13 ].…”
Section: Discussionmentioning
confidence: 77%